Inheritance of Mesotrione Resistance in an Amaranthus tuberculatus (var. rudis) Population from Nebraska, USA - Oliveira, Maxwel C.; Gaines, Todd A.; Jhala, Amit J.; Knezevic, Stevan Z. (Frontiers in Plant Science, 2018)
A population of Amaranthus tuberculatus (var. rudis) evolved resistance to 4-hydroxyphenylpyruvate dioxygenase (HPPD) inhibitor herbicides (mesotrione, tembotrione, and topramezone) in Nebraska. The level of resistance was the highest to mesotrione, and the mechanism of resistance in this population is metabolism-based likely via cytochrome P450 enzymes. The increasing number of weeds resistant to herbicides warrants studies on the ecology and evolutionary factors contributing for resistance evolution, including inheritance of resistance traits. In this study, we investigated the genetic control of mesotrione resistance in an A. tuberculatus population from Nebraska, USA. Results showed that reciprocal crosses in the F1 families exhibited nuclear inheritance, which allows pollen movement carrying herbicide resistance alleles. The mode of inheritance varied from incomplete recessive to incomplete dominance depending upon the F1 family. Observed segregation patterns for the majority of the F2 and back-cross susceptible (BC/S) families did not fit to a single major gene model. Therefore, multiple genes are likely to confer metabolism-based mesotrione resistance in this A. tuberculatus population from Nebraska. The results of this study aid to understand the genetics and inheritance of a non-target-site based mesotrione resistant A. tuberculatus population from Nebraska, USA.